Analysis of Implementation and Cloud Based ERP Implementation (Case Study of PT. Hologram Indonesia Kreatif) - Kartika Bangun; Y. Budi Susanto; Friska Natalia (ADI Publisher, 2020)
The development of increasingly sophisticated technology enables companies to take advantage of these technologies to compete by increasing the efficiency and effectiveness of the company. One technology that can improve this is ERP, which now consists of on premise and cloud based. One company that uses cloud based ERP named Apptivo, is PT. Hologram Indonesia Kreatif, where they aim to improve the performance of the sales marketing department, as well as finance. However, in its implementation, there are several obstacles. Using qualitative methods namely study cases and data collection with in-depth interviews, the authors found that there are three factors that play a role in these constraints, namely characteristics of individuals, characteristics of organizations and, characteristics of technology. In order to maximize the use of Apptivo, it can be suggested for companies that PT. Hologram Indonesia Kreatif can conduct training both in terms of business process or technical. In addition, companies can do roleplaying to familiarize users with Apptivo, as well as create a user guide or a kind of manual, for old or new users to read.